2017
DOI: 10.4172/2090-4924.1000127
|View full text |Cite
|
Sign up to set email alerts
|

Molecular Modeling and Docking Study of 2-Nitropropane Dioxygenase of Mycobacterium tuberculosis

Abstract: Mycobacterium tuberculosis is infectious bacteria and causes tuberculosis in humans. M. tuberculosis infects the immune deficient human and shows the symptoms of the infection. Also bacteria stay in latent phase inside the human body and can be active in suitable conditions. One third of the total population of the world is infected by M. tuberculosis; therefore it is very important to have potential drugs against tuberculosis. Mycobacteria have reported multidrug resistance to the available drugs for tubercul… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 7 publications
0
2
0
Order By: Relevance
“…Furthermore, the 3D verification showed that the predicted model was valid for the further docking process of Rv1250 protein of M. tuberculosis ( Abid et al, 2017 ). Following, results were concluded from the Verify-3D assessment model.…”
Section: Resultsmentioning
confidence: 93%
See 1 more Smart Citation
“…Furthermore, the 3D verification showed that the predicted model was valid for the further docking process of Rv1250 protein of M. tuberculosis ( Abid et al, 2017 ). Following, results were concluded from the Verify-3D assessment model.…”
Section: Resultsmentioning
confidence: 93%
“…The catalase-peroxidase enzyme (KatG) is used to activate the INH, a pro-drug. Then there is a reaction of resulting active species with NAD+ (Nicotinamide adenine dinucleotide) to develop an INH-NAD adduct, which impedes the enoyl acyl carrier protein reductase (InhA), causing the inhibition of mycolic acid biosynthesis and hence, the mycobacterial cell death ( Kumar & Jena, 2014 ; Abid et al, 2017 ). Mutation in KatG gene, a virulence determinant and activator of prodrug INH, is the chief mechanism of resistance of INH.…”
Section: Introductionmentioning
confidence: 99%